Implementasi Pendidikan Multikultural dalam Pembentukan Karakter Siswa Kelas IX di Sekolah Multikultural SMPS Sultan Iskandar Muda - Nadila Wanti; Rusydi Ananda; Nuriza Dora (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Multiculturalism is an understanding that emphasizes the equality and equality of local cultures without ignoring the rights and existence of other cultures, which is important for us to understand together in the life of a multicultural society like Indonesia. Multicultural education can be formulated as a form of awareness about cultural diversity, human rights as well as reducing or eliminating all types of prejudice or prejudice to build a just and advanced society. Multicultural education can also be interpreted as a strategy to develop awareness of a person's pride in their nation. The aims of this research are: (1) To determine the implementation of multicultural education at the SMPS Sultan Iskandar Muda Multicultural School; (2) To determine multicultural education in shaping the character of class IX students at the SMPS Sultan Iskandar Muda Multicultural School, and (3) To determine the impact of multicultural learning on the attitudes of class IX students at the multicultural school SMPS Sultan Iskandar Muda. In this research, the research method used is a qualitative approach and analytical descriptive methods. Data collection was carried out in 3 ways, namely, observation, interviews and documentation. The results of this research show that: (1) The implementation of multicultural education is carried out in various ways, the first is learning procedures, namely: Praying, seating arrangements for children, dividing groups, inserting multicultural values ​​in each subject, and teachers participating in emulating multicultural education, the second is a joint religion class program, and the third is a diversity chatbot program (2) With multicultural education, it can shape students' character starting by providing lessons about politeness and humanity, mutual respect, cooperation and tolerance, not discriminating, etc. -other. (3) The existence of multicultural learning has a very positive impact on yaoti by being disciplined, maintaining manners, not discriminating against ethnicity, race and characteristics. Students can appreciate differences so that there is no gap between one child and another, especially students at SMPS Sultan Iskandar Muda who have diversity.